RETRACTED: The teachings of Hurufism and Nasimi’s poetic skills - Amonova Zilola; Rajabova Marifat; Safarova Hilola; Shirinova Mekhrigiyo; Akhrorova Zufnunabegim (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001